THE MODEL OF EXTRACURRICULAR WORK WITH STUDENTS OF ENGINEERING SPECIALTIES - Valerii Vodovozov; Zoia Raud; Tetiana Detsiuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The subject of the research is the analysis of the development experience and the first phase of implementation of the model of extracurricular work with students of engineering specialties at Chernihiv National University of Technology (Ukraine), which was developed on the basis of the author's methodology ALM (active learning methods) at Tallinn University of Technology (Estonia) in combination with forms and methods of extracurricular work. The purpose of this model is to promote the enhancement of the motivation of students in engineering specialіties to succeed in learning. The main task of the research is to evaluate the readiness of students of engineering specialіties to participate in extracurricular activities and their awareness of the forms and methods of extracurricular work, the analysis of the first results of the implementation of the model of extracurricular work of students of engineering specialіties. For the observing stage of the experiment, such methods were used as theoretical, empirical, pedagogical experiment, mathematical and statistical methods. Participants were 92 students of the 3rd year of engineering specialіties of Chernihiv National University of Technology. Most students (82%) believe that extracurricular work has an impact on the formation of the individual and on the professional growth of a future specialist. The motivation for success among most respondents (73%) is average, 33% of respondents are not very good interlocutors who have shortcomings in communication; 60% have an average level of communication skills, 58% of respondents need to build self-confidence. Based on the received results from the questionnaire and tests carried out among students, a model of extracurricular work with students of engineering specialіties has been developed. The first stage of the implementation of this model has shown a positive dynamics. The model requires further testing and research of the impact on the students'personality.